Isolated Conjugated Hyperbilirubinemia in Seriously Ill Children - Don't Forget Sepsis! - Anirban Mandal; Amitabh Singh (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2016)
Background: Jaundice is frequently associated with extrahepatic systemic infections. The important causes include increased bilirubin levels due to hemolysis, hepatic dysfunction, reduced excretion and cholestasis. Sepsis induced cholestasis has a unique pathophysiologic basis. Although common in gram negative sepsis among neonates, the clinical features of sepsis induced cholestasis are not widely recognized older children. Case report: We present a 6 year old, premorbidly asymptomatic boy with community acquired MRSA sepsis-pneumonia and ARDS (Acute respiratory distress syndrome) with isolated conjugated hyperbilirubinemia. A diagnosis of sepsis induced isolated cholestasis was considered after ruling out other possible causes of cholestasis. The hyperbilirubinemia improved with improvement in the primary pathology. Conclusion: Early recognition of sepsis as a cause of isolated cholestatic jaundice would avoid unnecessary investigations and therapy would help in early institution of appropriate therapy.